Distribution of involved abdominal lymph nodes is correlated with the distance from the esophagogastric junction to the distal end of the tumor in Siewert type II tumors. Issue 10 (October 2015) - Mine, S.; Kurokawa, Y.; Takeuchi, H.; Kishi, K.; Ito, Y.; Ohi, M.; Matsuda, T.; Hamakawa, T.; Hasegawa, S.; Yoshikawa, T.; Hiki, N.
Abstract Background The optimal surgical approach for Siewert type II adenocarcinoma of the esophagogastric junction (AEG) has not yet been agreed. Here we investigated whether the distance from the esophagogastric junction (EGJ) to the distal end of the tumor was related to the distribution of involved abdominal lymph nodes in Siewert type II tumors. Methods A total of 288 patients with pT2-4 AEG Siewert II, treated by R0 surgical resection at 7 institutions in Japan, were retrospectively investigated. The distribution of involved abdominal nodes was correlated with the distance from the EGJ to the distal end of the tumor. Results In patients where the distance from the EGJ to the distal end of the tumor was ≤30 mm, the frequency of nodal involvement along the greater curvature or antrum was low (2.2%). In contrast, in patients where the distance was >50 mm, the incidence of this nodal involvement was 20.0%. In patients where the distance was 30–50 mm incidence was intermediate (8.0%). Multivariate analyses showed that the distance from the EGJ to the distal end of the tumor was significantly related to lymph node involvement along the greater curvature or antrum (odds ratio 3.7, 95% confidence interval 1.3–11, p = 0.006). Conclusions When the distance from the EGJ to the distal end of the tumor is ≤ 30 mm for Siewert II AEG, esophagectomy or proximal gastrectomy is sufficient from the point of view of abdominal lymphadenectomy. However, a total gastrectomy should be considered for abdominal lymphadenectomy when this distance is > 50 mm.